Criminalistics characteristics of crimes against justice (theoretical aspect) - Ahmadov, Vusal Alyhismet (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article highlights the main theoretical foundations of the forensic characteristics of crimes against justice. The theoretical and legal analysis of individual factors and causes of crime against justice is carried out. The crimes against justice are characterized by high latency, which is due to the high level of corporatism, the desire to prevent public disclosure of existing facts of unjust decisions, pressure on witnesses, falsification of evidence, forceful testimony it is determined, etc. A theoretical model of special-criminological prevention of crimes against justice is proposed. All elements of the theoretical model are inextricably linked, and scientific support should be carried out at every stage, from obtaining the necessary information by relevant actors and ending with the evaluation of the effectiveness of preventive activities. The elements of the theoretical model are inextricably linked should be implemented at the general social level of prevention of crimes against justice and at the special criminological level of prevention of crimes of the analyzed type it is noted. It is noted that crimes against justice differ significantly from other types of crimes. First of all, the principle of corporate solidarity of lawyers operates, which is why the overwhelming majority of complaints of victims of illegal detention, forced to testify, remain unaddressed, or only result in a disciplinary sanction, without opening criminal proceedings and transferring the case to court. The prevention of crimes against justice should take place along several main lines: careful selection, education and training of staff; further improvement of the law enforcement system; implementation of the system of witness protection measures provided by law, as well as measures to protect investigators, prosecutors and judges; steady fight against corruption in the legal system and pressure on its employees; ensuring the inevitability of liability of persons who try to force them to such violations; legal and moral education of the population in the spirit of respect for the law and intolerance of offenders it is determined.